جهود النحويين القدامى في تأسيس الحدود النحوية - عوض سامي; عبود يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
لا بدّ لكلّ علم من علوم الإنسانية من وضع مصطلحات تخصّه ، ينفرد بها عن غيره من العلوم وفق منهج واضح يفسّرها ويشرح ألفاظها ، تشكّل في نهاية المطاف تعريفات جامعة مانعة ، لها شروطها وأحكامها وضوابطها تُعرفُ باسم الحدود . تطمحُ الدراسة الآتية إلى تعريف القرّاء بملامح الوعي النقدي لمصطلح الحدود النحوية ، حيث تتناولُها على مستويين : المستوى الأول يغطي بالدراسة مرجعية هذا المصطلح والأسس التي يبنى عليها في الدراسات الإنسانية ، ثم يفتش عن عوامل نشأته ، ويضيء جوانب تطوّره عند أهم نحاتنا القدامى . كما يستخلص الشروط اللازمة لبناء الحدّ في النحو . أما المستوى الثاني فيتكامل معه ويعززه بالأمثلة التطبيقية حيث يثمّن الجهود التي بذلها النحويون العرب في تشييد حدود مصطلحاتهم النحوية ، ويبين أوجه التجديد في صناعتها وفق الأسس الموضوعية والشروط العلمية التي يرتكز عليها بناء الحد . ثم ختمت هذه الدراسة بأهم النتائج التي توصلت إليها . Each branch of humanity sciences must have its own terminology، which differ from others according to plain method in which its vocabulary must be interpreted and explained ، eventually this vocabulary must form specific comprehensive definitions ، which has its rules and codes as we defined "limits" . The following research aspire to define the readers with the critical awareness features of grammatical limits ، where handles through two levels: The first level ،through its studies، covers the authority of the idiom and the bases of the human studies ، then turns to prescribe the grammatical limits ، then he looks for the elements of its growing up، and throws light on the aspects of its development by our important ancient grammatists . Whereas the second level completes and promotes the first with practical examples in which it evaluates the efforts the Arab grammarians exert in building limits in their grammatical terminology .it shows the aspects of the renewal in its industry according to the objective rules and scientific condition limit building depends on . Thereby to seal the most important research results .